Filamentation-driven peripheral clustering of the inducible lysine decarboxylase is crucial for E. coli acid stress response - Moritz A. Kirchner; Jessica El Khoury; Frédéric Barras; Jean-Philippe Kleman; Irina Gutsche (Communications Biology)
Abstract Bacteria use sophisticated acid stress response strategies to withstand fluctuating environmental pH, with enterobacterial inducible amino acid decarboxylases playing a major role. The lysine decarboxylase LdcI catalyses lysine-to-cadaverine conversion coupled to proton consumption and carbon dioxide release, thereby buffering cytoplasmic and extracellular pH. Our previous studies showed that Escherichia coli LdcI forms intracellular patches under mild acid stress, and that purified LdcI polymerises into filaments at acidic pH. Here, we investigated the physiological relevance of LdcI filamentation using 3D super-resolution microscopy and an LdcI polymerisation-deficient E. coli mutant strain. We established a semi-automated workflow for intracellular cluster detection and quantitative analysis, and demonstrated predominantly peripheral clustering of LdcI. Disrupting LdcI polymerisation markedly reduced cluster size without significantly affecting localisation, suggesting that clustering is driven by filamentation. Growth and pH measurements revealed that the mutant exhibits reduced fitness and impaired extracellular buffering compared to the wild type, indicating that LdcI polymerisation enhances the E. coli capacity to counteract acid stress without affecting intracellular location of the enzyme. Our findings provide strong evidence that LdcI filamentation regulates acid stress response by spatially optimising enzymatic activity. More broadly, this work supports the functional significance of metabolic enzyme self-assembly in bacterial stress adaptation.